Gamification-Based Redesign of Sekawan V3 Using User-Centered Design and Usability Evaluation - Fadhlan Putera Sopian; Chanifah Indah Ratnasari (Komunitas Dosen Indonesia, 2026)
Higher education institutions expect thesis administration systems to support students not only functionally but also through clear workflow guidance and sustained engagement. In Sekawan V3, preliminary observation and an initial user interview identified issues related to limited progress visibility, fragmented workflow, unclear status feedback, and low motivational support during the undergraduate thesis process. This study aimed to redesign Sekawan V3 by integrating gamification elements based on the Octalysis framework into its interface while grounding the redesign in a user-centered design approach. The novelty of this study lies in applying gamification to a procedural academic administrative workflow to improve progress awareness and user motivation in thesis administration. The study consisted of four main stages: understanding the context of use, specifying user requirements, producing design solutions, and evaluating the resulting prototype. A high-fidelity prototype was developed in Figma by redesigning the main thesis administration features, including Dashboard, Files, Logbook, Progress Check, and Leaderboard. The gamification system was implemented through progress indicators, levels, badges, and task guidance. A usability evaluation was conducted through online unmoderated testing with 26 respondents (17 active students and 9 alumni), followed by the System Usability Scale questionnaire. The results showed an overall SUS score of 72.79, categorized as an acceptable usability level with a good user experience rating. These findings suggest that the gamification-based redesign can improve progress awareness, workflow clarity, and motivational support in thesis administration, while still requiring further refinement and full backend implementation.